2023
DOI: 10.1038/s41598-023-45398-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of antibiotic prophylaxis with intracameral cefuroxime on postoperative infectious endophthalmitis rates in a high-volume cataract surgery center

Luciane Nunes de Sousa Casavechia,
Antonio Carlos Meireles,
Evandro Schapira
et al.

Abstract: Our purpose was to compare postoperative infectious endophthalmitis rates before and after the introduction of antibiotic prophylaxis via intracameral with cefuroxime (ATB-P IC) in a high-volume cataract surgery service. Retrospective cohort study considering patients who underwent cataract surgery at Ophthal Hospital Especializado, São Paulo, Brazil, from January/2011 to December/2019. Patients operated from 2013 to 2019 comprised the ATB-P IC group while those operated from 2011 to 2013 formed the control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Another RCT studied intracameral 0.5% moxifloxacin and reported that intracameral moxifloxacin was associated with a reduced rate of endophthalmitis [ 94 ]. In addition, many retrospective series and prospective studies have reported benefits with intracameral antibiotic prophylaxis in cataract surgery [ 88 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. Further, several meta-analyses have also supported the use of intracameral antibiotics, highlighting a greater effectiveness of this route as a prophylactic measure and a lack of additional benefits from topical antibiotic administration [ 100 , 105 , 106 ].…”
Section: Current Prophylactic Measures and Management Approachesmentioning
confidence: 99%
“…Another RCT studied intracameral 0.5% moxifloxacin and reported that intracameral moxifloxacin was associated with a reduced rate of endophthalmitis [ 94 ]. In addition, many retrospective series and prospective studies have reported benefits with intracameral antibiotic prophylaxis in cataract surgery [ 88 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. Further, several meta-analyses have also supported the use of intracameral antibiotics, highlighting a greater effectiveness of this route as a prophylactic measure and a lack of additional benefits from topical antibiotic administration [ 100 , 105 , 106 ].…”
Section: Current Prophylactic Measures and Management Approachesmentioning
confidence: 99%